Analysis of Phytoplankton Structure Community, Water Quality and Cultivation Performance in Litopenaeus vannamei Intensive Pond Located in Tembokrejo Village, Muncar, Banyuwangi - Katmoko, Gesang Maulana Dwi; Risjani, Yenny; Masithah, Endang Dewi (Graduate School, Universitas Brawijaya, 2021)
Phytoplankton plays an important role in Litopenaeus vannamei cultivation. It plays a role as natural feed, water quality control, and indicator of shrimp cultivation success. The community structure of phytoplankton can be influenced by organic matter concentration in ponds. On the other hand, water quality and phytoplankton community structure also influence the productivity of shrimp cultivation. The research aimed to analyze the phytoplankton structure community, cultivation performance and the water quality in one of vananmei shrimp cultivation located in Muncar District. The research used the descriptive method. The research was conducted in two shrimp intensive system ponds in Tembokrejo Village, Muncar District, Banyuwangi, on February-March 2020. Parameters observed were composition, diversity, and density of phytoplankton, water quality parameters, and production performance in each pond. Based on the results, five phytoplankton classes was found: Bacillariophyceae (12 genera), Chlorophyceae (4 genera), Cyanophyceae (8 genera), Dinophyceae (2 genera), and Euglenophyceae (1 genus). Based on the density, Cyclotella and Chlorella were dominated in both ponds. Diversity index values on ponds 1 and ponds 2 were 1.64 and 1.71, respectively. The productivity of both ponds was 10.794 kg.ha-1 and 11.698 kg.ha-1, FCR (Feed Conversion Ratio) were 0.99 and 1.18, and ADG (Average Daily Growth) on both ponds were 0.16 g.day-1. Water quality parameters in both ponds showed an optimal range for vannamei cultivation, except phosphate, which is quite high. Overall, the cultivation performance of both ponds in our research showed good results. However, cultivation performance obtained in this research was not on its best performance yet due to Infectious Myonecrosis (IMNV) infection.Keywords: Cultivation performance, Litopenaeus vannamei, muncar, phytoplankton.